Tratamiento contable de la nic 16 en empresas constructoras del cantón santo domingo. - Balarezo Cisneros, Kely Vanessa (2025)
The International Accounting Standards IAS 16 allows for the identification, valuation, and accounting of property, plant, and equipment assets in companies and is mandatory in Ecuador. The objective is to establish compliance with IAS 16 in construction companies in the Santo Domingo canton regarding the valuation of assets (Property, Plant, and Equipment). The methodology has a qualitative-quantitative approach, with a non-experimental cross-sectional design; the analytic-synthetic method was employed; the sample was non-random and non-probabilistic due to convenience, consisting of 10 construction companies in the Santo Domingo canton, to which a survey was applied to their accountants. As a result, it was found that the majority of the construction companies surveyed in the Santo Domingo canton adhere to the guidelines set forth in the standards for the treatment of Property, Plant, and Equipment IAS 16; both for the identification, valuation, and accounting of the assets. However, some aspects must be reviewed, such as relocation costs and the recognition of expenses for repairs and maintenance of an asset, which do not align with what is indicated in IAS 16.